2007
DOI: 10.2208/jsceja.63.423
|View full text |Cite
|
Sign up to set email alerts
|

Vibration-Based Damage Detection in Flexible Risers Using Time Series Analysis

Abstract: In this paper, a statistical pattern recognition method based on time series analysis is implemented in flexible risers. This method uses a combination of Auto-Regressive (AR) and Auto-Regressive with eXogenous inputs (ARX) prediction models. The flexible riser model used in this paper is experimentally validated employing a proposed numerical scheme for dynamic response of flexible risers. A modal-based damage detection approach is also implemented in the flexible riser model and its results are compared with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 15 publications
(15 reference statements)
0
4
0
Order By: Relevance
“…Similarly, a modal distribution method was proposed by Sweetman et al [16], which uses the change between the power spectrums from measured structural responses to indicate damage in the primary system; the method is a frequency domain method based on output data, which is not suitable to deepwater risers with time varying natural frequencies. Riveros et al [17] concluded that a statistical pattern Pipeline failure statistics recognition method with a combined model with auto-regressive (AR) and auto-regressive with exogenous inputs (ARX) works better than a modal distribution method. However, in deepwater, the inputs are unknown, which means the method is not suitable.…”
Section: Methods For Riser Damage Detectionmentioning
confidence: 99%
“…Similarly, a modal distribution method was proposed by Sweetman et al [16], which uses the change between the power spectrums from measured structural responses to indicate damage in the primary system; the method is a frequency domain method based on output data, which is not suitable to deepwater risers with time varying natural frequencies. Riveros et al [17] concluded that a statistical pattern Pipeline failure statistics recognition method with a combined model with auto-regressive (AR) and auto-regressive with exogenous inputs (ARX) works better than a modal distribution method. However, in deepwater, the inputs are unknown, which means the method is not suitable.…”
Section: Methods For Riser Damage Detectionmentioning
confidence: 99%
“…19 However, the vast majority of these studies have primarily treated the data from each sensor as an independent measurement to construct scalar autoregressive (AR) models. 7,9,16,[19][20][21][22][23][24] Mattson and Pandit 25 proposed a method based on ARV models and using the statistical moments of the residuals of these models as damage-sensitive features. Vector models allow a particular series to be described not only in terms of its own past values, but also in terms of the past values in the other sensors, and provides a thorough description of the interaction between response sensors.…”
Section: Statistical Damage Detection Motivationmentioning
confidence: 99%
“…Bao et al 17 used the autoregressive moving average (ARMA) model for the response analysis of submarine pipelines. Similar to the work of Riveros et al, 16 the Mahalanobis distance between the AR model coefficient vector obtained from the healthy and damaged structure is used as the damage indicator. Besides, a realistic experimental simulation of ambient excitations was attempted by placing a 10-m long pipeline in a water tank so that random wave loading following a JONSWAP spectrum was generated.…”
Section: Introductionmentioning
confidence: 99%
“…The time series analysis methods have also been used for the damage identification of deepsea risers. Riveros et al 16 combined the AR and ARX models to fit the responses of an experimental riser. A statistical pattern recognition method with the estimated AR coefficients was used to detect and locate the structural deterioration of the riser due to fatigue damage.…”
Section: Introductionmentioning
confidence: 99%